2020
DOI: 10.1523/eneuro.0016-20.2020
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid Adaptation to Changing Mechanical Load by Ordered Recruitment of Identified Motor Neurons

Abstract: As they interact with their environment and encounter challenges, animals adjust their behavior on a moment-to-moment basis to maintain task fitness. This dynamic process of adaptive motor control occurs in the nervous system, but an understanding of the body's biomechanics is essential to properly interpret the behavioral outcomes. To study how animals respond to changing task conditions, we used a model system in which the functional roles of identified neurons and the relevant biomechanics are well understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 74 publications
2
25
0
Order By: Relevance
“…The animal's vision is poorly developed and the smell or the superficial texture of the seaweed are unreliable predictors of its biomechanical properties, such as toughness or size. The different kinds of seaweeds it feeds on not only vary dramatically in these biomechanical properties before the animals arrive, but they can also change in response to herbivory, or once the animal has started to ingest [126][127][128][129]. Therefore, Aplysia has no other choice than trying out how to best ingest the seaweed it is encountering.…”
Section: Fig 5: Aplysia Feeding Movements Vary Both Within and Betwementioning
confidence: 99%
See 1 more Smart Citation
“…The animal's vision is poorly developed and the smell or the superficial texture of the seaweed are unreliable predictors of its biomechanical properties, such as toughness or size. The different kinds of seaweeds it feeds on not only vary dramatically in these biomechanical properties before the animals arrive, but they can also change in response to herbivory, or once the animal has started to ingest [126][127][128][129]. Therefore, Aplysia has no other choice than trying out how to best ingest the seaweed it is encountering.…”
Section: Fig 5: Aplysia Feeding Movements Vary Both Within and Betwementioning
confidence: 99%
“…Therefore, Aplysia has no other choice than trying out how to best ingest the seaweed it is encountering. This process manifests itself not only in a high variability of behavioral parameters between each feeding attempt [20,[130][131][132][133], but also during each attempt [126,134,135].…”
Section: Fig 5: Aplysia Feeding Movements Vary Both Within and Betwementioning
confidence: 99%
“…Analysis of experimental data was aided by the Python package neurotic (NEURoscience Tool for Interactive Characterization) [48], and analysis procedures were similar to those described by [47]. Briefly, spikes were detected using window discriminators.…”
Section: Experimental Methods and Data Analysismentioning
confidence: 99%
“…Amplitude thresholds were determined manually. Spikes were grouped into bursts using firing frequency criteria (see [47] for details; for B7, the burst initiation and termination frequencies were 20 Hz and 10 Hz, respectively, based on observations by [154,155]). Video was used to determine the timing of inward movement of food during swallowing and outward movement of tubing during rejection.…”
Section: Experimental Methods and Data Analysismentioning
confidence: 99%
“…Additionally, both parameters have similar influence on the variance of the cycle length. Recent work has shown that the feeding CPG of the marine mollusk Aplysia californica recruits additional motor neurons when the organism encounters unexpected resistance in swallowing food [17,18], and that variability of motor neuronal activity is reduced for those components of feeding behavior that matter most for task fitness [11]. Although the isolated three pool model considered here lacks important circuit components (such as sensory feedback [10]), the relative sensitivity of the cycle time variance to µ versus Ω could nevertheless suggest experimentally testable questions.…”
Section: Extinction Times In the Minimal Modelmentioning
confidence: 99%